Enhanced fluorescence of starch-fluorescence guest complexes enables evaluation of the encapsulation properties of maize starches. (February 2017) - Wang, Shixiu; Zhan, Jinling; Jin, Zhengyu; Tian, Yaoqi
Abstract: In this study, high-amylose maize starch (HAMS) was mixed with salicylic acid, 1-naphthol, and 2-naphthol, and the physical mixtures were then subjected to a sealed-heating procedure to prepare HAMS-fluorescence guest complexes. The results, obtained from wide angle X-ray scattering and thermogravimetric analysis, showed that all three fluorescence guests were encapsulated in the hydrophobic cavity of HAMS. After screening, salicylic acid was chosen as the most suitable fluorescent probe for evaluating the properties of the starch helix cavity. The formation of a starch-salicylic acid inclusion complex was accompanied by increased fluorescence from the salicylic acid molecules included in the complex. The hydrophobicity of the starch helix cavity and the capability of starch to form inclusion complexes could be evaluated from the increasing intensity of the fluorescence. Accordingly, the capabilities of maize starches to form inclusion complexes followed the order: high-amylose maize starch > normal maize starch > waxy maize starch. Graphical abstract: Highlights: Fluorescent probes were successfully encapsulated in the helix cavity of HAMS. Salicylic acid (SA) was chosen as the most suitable fluorescent probe. The starch-SA inclusion complex indicated an increasing fluorescence. The capability of maize starches to form inclusion complexes was evaluated.